Tingkat Pengetahuan Siswi SMA Muhammadiyah Palangka Raya tentang Dysmenorrhea: Level of Knowledge of Female Students in Muhammadiyah Senior High School of Palangka Raya about Dysmenorrhea - Syahrida Dian Ardhany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Dysmenorrhea is one of the most common gynecological problems in women of all ages, the incidence of dysmenorrhea in the world is very large on average more than 50% of women in every world experience it. Muhammadiyah Senior High School is one of the best schools in Palangka Raya. Based on the observations that have been done by researcher the results are many students got dysmenorrhea with severe pain and certainly this condition will disrupt daily activity, especially when teaching and learning and so extracurricular activities. Therefore, research about the level of dysmenorrhea knowledge is needed. The research method was used in this research was a descriptive method with the technique of sampling purposive sampling with 10 statements questionnaire consist of 4 indicators there is the definition of dysmenorrhea, signs, and symptoms of dysmenorrhea, causes of dysmenorrhea and how to treat and prevent dysmenorrhea. Based on the results of the study was found that the level of dysmenorrhea knowledge female students Muhammadiyah Senior High School of Palangka Raya included in the sufficient category with percentage 66,67%, meanwhile based on knowledge indicators, definition of dysmenorrhea was 73.22% (sufficient category), signs and symptoms of dysmenorrhea was 58.93% (sufficient category), causes of dysmenorrhea was 63.69% (sufficient category) and how to treat and prevent dysmenorrhea was 68.75% (sufficient category). Based on the results of this study, it can be concluded that the level of dysmenorrhea knowledge female students Muhammadiyah Senior High School of Palangka Raya included in category sufficient to know with percentage 66.67%.